George Eliot and the conflict of interpretations a reading of the novels - Carroll, David 1932- (Cambridge University Press, 1992)
Two versions of George Eliot, both influential, have emerged from the study of her life and work. One is the radical Victorian thinker, formidably learned in a whole range of intellectual disciplines; the other is the reclusive novelist, celebrating through her fiction the communal values which were being eroded in the modern world. This chronological study of the novels brings the two together and places her within the crisis of belief and value acted out in the mid-nineteenth century. George Eliot saw this crisis as one of interpretation, in a vivid, almost apocalyptic awareness that traditional modes of interpreting the world were breaking down irrevocably. This study shows how, in response, she redefined the nature of Victorian fiction, testing to the point of destruction a variety of Victorian myths, orthodoxies and ideologies in each of her novels
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Eliot, George / 1819-1880 / Criticism and interpretation; Eliot, George -- 1819-1880; Geschichte 1800-1900; Geschichte; Women and literature / England / History / 19th century; Didactic fiction, English / History and criticism; Roman